2019
DOI: 10.3389/fphys.2019.00903
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Water- and Land-Based Exercise Training Comparably Improve Exercise Capacity and Vascular Function in Patients After a Recent Coronary Event: A Pilot Randomized Controlled Trial

Abstract: Background We hypothesized that a 2-week twice daily aquatic endurance plus calisthenics exercise training program: (i) increases aerobic exercise capacity (peak oxygen uptake/ O 2 peak), (ii) improves endothelium-dependent flow-mediated vasodilation (FMD), and (iii) reduces circulating markers of low-grade inflammation and hemostasis, as compared to land-based endurance plus calisthenics exercise trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 47 publications
4
44
0
3
Order By: Relevance
“…These findings suggest that aquatic exercise could have similar CVD risk reduction benefits to land-based exercise in this population. Although this study is a cross-sectional study and outcomes were not measured over time, our findings are in agreement with work by others ( Sherlock et al, 2014 ; Cugusi et al, 2019 ; Vasić et al, 2019 ). This study provides support for the CVD risk-reduction role of aquatic exercise and highlights a potential next step, which would be developing a cohort study to measure changes in circulatory function over time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings suggest that aquatic exercise could have similar CVD risk reduction benefits to land-based exercise in this population. Although this study is a cross-sectional study and outcomes were not measured over time, our findings are in agreement with work by others ( Sherlock et al, 2014 ; Cugusi et al, 2019 ; Vasić et al, 2019 ). This study provides support for the CVD risk-reduction role of aquatic exercise and highlights a potential next step, which would be developing a cohort study to measure changes in circulatory function over time.…”
Section: Discussionsupporting
confidence: 92%
“…Our study indicates that long-term, water-based exercise in older individuals can offer improvements in macrovascular function parameters, which are associated with CVD risk reduction, such as %FMD (Klonizakis et al, 2017). This happens in a manner similar to what is observed in the short-term, in clinical populations such as people with coronary heart disease (Vasić et al, 2019) and osteoarthritis (Alkatan et al, 2016). Our work extends the findings of other research groups on clinical (e.g., peripheral artery disease) (Park et al, 2019) and general (Sherlock et al, 2014;Reichert et al, 2018) populations, which have used alternative measures known to be related to CVD risk, such as arterial stiffness (assessed by Pulse Wave Velocity) (Sherlock et al, 2014) and blood pressure (Reichert et al, 2018), suggesting notable risk reductions, similar to that observed following land-based exercise (Di Francescomarino et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Patients with CAD following a 6-month aerobic exercise training program had higher peak response to acetylcholine when they performed high-frequency exercise compared with low frequency cardiac rehabilitation programs[ 130 ]. In addition, a 2-wk twice daily aquatic endurance plus calisthenics exercise training program in patients with a recent myocardial infarction or revascularization intervention improved both aerobic exercise capacity and vascular endothelial function[ 131 ]. Kollet et al [ 132 ] conducted a randomized pilot study and enrolled post-myocardial infarction patients undergoing PCI who performed a 30-min moderate-intensity aerobic training program.…”
Section: Exercise and Coronary Artery Diseasementioning
confidence: 99%